Referral and termination issues for counsellors - Leigh, Anne (Professional skills for counsellors., 1998)
This work stresses the need to be aware of limits of competency legal issues and ethics, and to recognize the value of local resources. Leigh includes guidelines for receiving referrals from outside agencies and effective referral.